2013
DOI: 10.5455/medarh.2013.67.407-409
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Remifentanil/Propofol Anesthesia on Ventilator-associated Pneumonia Occurence After Major Cardiac Surgery

Abstract: The study is designed to evaluate the influence of remifentanil/propofol anesthesia on ventilator-associated pneumonia (VAP) occurrence and respiratory support (RS) time after major cardiac surgery.Material and methods:In retrospective-prospective study we investigated the respiratory support time and VAP occurrence in group of 47 patients with remifentanil/propofol and 35 patients with fentanil/midazolam anesthesia after major cardiac surgery in period June 2009–December 2011. Groups are divided in subgroups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 9 publications
(11 reference statements)
1
6
0
Order By: Relevance
“…In our study the incidences of pneumonia was significantly lower in the LVAD ultra group versus the LVAD match group. These findings support those of Kurihara et al and Kradzalic et al [ 27 , 28 ], who demonstrated a lower incidence of ventilator-associated pneumonia after FTA. Despite that the incidence of sepsis did not differ significantly between the two matched groups, a tendency for lower incidence of sepsis in the LVAD ultra could be detected ( p = 0.055).…”
Section: Discussionsupporting
confidence: 92%
“…In our study the incidences of pneumonia was significantly lower in the LVAD ultra group versus the LVAD match group. These findings support those of Kurihara et al and Kradzalic et al [ 27 , 28 ], who demonstrated a lower incidence of ventilator-associated pneumonia after FTA. Despite that the incidence of sepsis did not differ significantly between the two matched groups, a tendency for lower incidence of sepsis in the LVAD ultra could be detected ( p = 0.055).…”
Section: Discussionsupporting
confidence: 92%
“…37,38 Use of anesthetic agents that are more rapidly eliminated may reduce length of respiratory support duration and can prevent development of ventilator-associated pneumonia in obese patients. 39 In this study, obesity was a protective factor for bleeding, as obese patients were less likely to receive blood products. Similar findings have been reported in prior studies.…”
Section: Colour Online Colour Onlinementioning
confidence: 75%
“…Perioperative physiotherapy was found to decrease the prevalence of postoperative pneumonia in high‐risk patients and is strongly recommended by some studies . Use of anesthetic agents that are more rapidly eliminated may reduce length of respiratory support duration and can prevent development of ventilator‐associated pneumonia in obese patients …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown that a delay in the initiation of appropriate antibiotic therapy for patients with VAP has association with increased morbidity, cost of care, and mortality whether VAP is early or late in onset [ 30 , 31 ]. Therefore, once a patient is diagnosed with VAP, broad-spectrum antibiotic therapy should be adopted immediately targeting specific likely pathogens based on timing of VAP onset and modified by knowledge of local patterns of antibiotic resistance.…”
Section: Reviewmentioning
confidence: 99%